A COMPARATIVE AND PROSPECTIVE STUDY OF VENTRAL HERNIA REPAIR BY LAPAROSCOPIC AND OPEN TECHNIQUE - Satya Prakash Prajapati; Rahul Patel; Ashirvad Datey; Krishna Kumar Bharang (International Journal of Health and Clinical Research, 2021)
Background: We aimed to compare duration of surgery, post-operative pain, post-operative complication, cosmesis, hospital stay after laparoscopic and open repair technique. Methodology:The study was conducted as a prospective observational study on patients presenting with ventral hernia at tertiary care centre. Patients were then randomized into 2 groups based upon types of surgery i.e. Laparoscopic and open mesh hernia repair Immediately post-operatively, pain assessment was done using VAS. Patients were followed up till discharge thereafter monthly till 6 months. Length of stay in Hospital was noted and days to return to normal activities were documented along with presence of immediate and longterm complication. Results: A total of 60 patients with ventral hernia who underwent surgery were included, of them, laparoscopic repair was done in 25 (41.7%) whereas open repair was done in 35 (58.3%) patients. Mean duration of surgery in laparoscopic was 90.52±12.653 minutes whereas duration was 59±9.139 in open repair. We observed a significantly prolonged duration of surgery, shorter duration of post operative pain, lower incidence of seroma, early post operative ambulation, short duration of hospital stay early return to normal activity and better cosmesis in laparoscopic surgery group as compared to open surgery (p<0.05). Conclusions: Elective ventral hernias can be managed using both open as well as laparoscopic surgery. Laparoscopic hernia repair is superior to open hernia repair in terms of low post operative pain, early ambulation, low complication such as seroma, early return to normal activity, less hospital stay and achieving good cosmetic results.